Insights into the late-Sixties taxocenosis of Oniscidea from the Pontine islands (West Mediterranean) (Peracarida: Isopoda) - Gentile, Gabriele; Argano, Roberto; Taiti, Stefano (Fragmenta entomologica, 2019)
We report and discuss faunistic data of Oniscidea inhabiting the Pontine islands, a group of five small volcanic islands and several islets in the Tyrrhenian Sea, located about 60 km from the Italian mainland. Data here presented were primarily obtained from the examination of the material collected during a three-year (1965-1968) research program supported by the Italian National Council of Research and aimed at investigating Mediterranean small island faunas, including Oniscidea. Despite the sampling was not specifically directed at Oniscidea, these data may provide insights into the structure of the Oniscidean taxocenosis of the islands as it existed fifty years ago. Thirty-five species belonging to 11 families, 8 ecological and 7 biogeographical classes were found on these islands. Such number of species of Oniscidea is very high, if we consider the low number of islands and their small sizes. Changes in climate and environmental conditions occurred in the last fifty years would call for a new investigation.